Identification of Hazardous Points on Highway 2076 Phosrisuwan District, Sisaket Province by using Rate Quality Control - Kumphan, Thipsuda (Srinakharinwirot University Engineering Journal, 2021)
The aim of this research was to rank No. 2076. The annual average daily traffic data were collected between B.E. 2560–2562 by using data from the Department of Highways, and the accident statistics were collected by using data from the Road Accident Victims Protection Company Limited. The rate quality control method and the dangerous factor (DF) calculating were used for ranking the hazardous points. The DF values of all phases on this highway were below 1. The highest value was shown at 0.66 in the Siao sub district area. The highest value of a phase on this highway was 0.68 at km. 42 – 43. From the results, the hazardous points on this highway were not in critical periods or required special supervision. However, the risk points of accidents on this highway must be improved. Hiyari – Hatto theory was used for identifying the risk points. People in the area identified the risk points into the Hiyari map. There were 4 risk points that need to be improved and analyzed the physical characteristics on the Highway No. 2076 to be a guideline for solving the risk points and to effectively create a safety road for all users.